Tool wear and life span variations in cold forming operations and their implications in microforming - Castagne, Sylvie J. (2018)
The current paper aims to review tooling life span, failure modes and models in cold microforming processes. As there is nearly no information available on tool-life for microforming the starting point was conventional cold forming. In cold forming common failures are (1) over stressing of the tool; (2) abrasive wear; (3) galling or adhesive wear, and (4) fatigue failure. The large variation in tool life observed in production and how to predict this was reviewed as this is important to the viability of microforming based on that the tooling cost takes a higher portion of the part cost. Anisotropic properties of the tool materials affect tool life span and depend on both the as-received and in-service conditions. It was concluded that preconditioning of the tool surface, and coating are important to control wear and fatigue. Properly managed, the detrimental effects from surface particles can be reduced. Under high stress low-cycle fatigue conditions, fatigue failure form internal microstructures and inclusions are common. To improve abrasive wear resistance larger carbides are commonly the solution which will have a negative impact on tooling life as these tend to be the root cause of fatigue failures. This has significant impact on cold microforming.